Verbal-visual aphorism - Nigro, Carlos (2020)
Under the stress caused by the coronavirus pandemic, reflection on life and self-care is strengthened. New interactions are made possible, in the heart of the desiring being and his microcosm, which makes his daily life a task force for self-knowledge and for schizoanalysis, in the face of nudity in face of the threats posed, whether real or imaginary. It enhances the subjectivity of the creative being that pulsates abstract time and space.